A Review on Islamic Microfinance Literature - Izzani Ulfi; Ujang Syahrul Mubarrok; Tjiptohadi Sawarjuwono; Bayu Arie Fianto (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
This research aims to discuss the bibliometric characteristics of Islamic microfinance using the Scopus database. This paper also provides recommendations on potential subjects for further study and development. There were 172 data analyzed through bibliometric analysis using the VOSviewer software, which enables the display of visualized patterns, such as the co-authorship and co-occurrence of keywords. The result indicated that Islamic Microfinance studies are still limited compared to other topics such as Islamic banks. Therefore, the issue can be overcome by developing a special journal, which focuses on Islamic Microfinance. Several topics were outlined based on the identified topic trends in keywords as references that can be developed for future research. These are the role of Islamic Microfinance related to COVID-19, the development of the halal industry in SMEs, and conflict of interest studies in Islamic Microfinance. This study also highlights the literature on Islamic microfinance specifically on the Indonesian context and its potential forthcoming topic to discuss.